Does the instability of economic development affect the elasticity of the labour market? - Monika Daňová; Ivana Kravčáková Vozárová (Review of Economic Perspectives, 2021)
Despite extensive research, the estimates of changes in employment are heter-ogeneous in different conditions of economic development. In this study, we examined the impact of the instability of economic growth on the elasticity of the labour market in a set of EU27 member states in the period 2000Q1-2019Q4.The sensitivity of the labour market was quantified in parallel by two available methods which are used for this pur-pose - by calculating the values of the arc elasticity coefficient and by regression analysis. Logarithmic linear regression models were compiled according to the analysis criteria individually for each member state. By comparing the values of the obtained elasticity indicators, differences in the responses of the labour market were identified. Our results show that the heterogeneity of opinions is to some extent natural. The elasticity of the labour market determined by calculating the values of the elasticity coefficient is charac-terized by a high variability of values. Similarly, the values of the regression coefficient reflect the nature of the macroeconomic development of the period under review. Accord-ing to our findings, the frequent short-term trends of negative economic development result in a reduced sensitivity of the labour market to the changes in economic perfor-mance, manifested by a lower employment elasticity compared to its values in economies with a stable development trend. Based on this, we formulate the connection between the elasticity of the labour market and the positive and negative economic development. We condition the sensitivity of the labour market to the changes in the trend of economic development with the occurrence of longer-lasting trends of negative economic develop-ment.
Keywords: E24; F43; J40; O47; R11; 330; economic growth; elasticity; employment; labour market; stability of devel-opment trend